Potential of Black Phosphorus in Immune-Based Therapeutic Strategies - Wenjuan Dong; Hu Wang; Hailin Liu; Chunqiao Zhou; Xuelin Zhang; Song Wang; Lin He (Bioinorganic Chemistry and Applications)
Black phosphorus (BP) consists of phosphorus atoms, an essential element of bone and nucleic acid, which covalently bonds to three adjacent phosphorus atoms to form a puckered bilayer structure. With its anisotropy, band gap, biodegradability, and biocompatibility properties, BP is considered promising for cancer therapy. For example, BP under irradiation can convert near-infrared (NIR) light into heat and reactive oxygen species (ROS) to damage cancer cells, called photothermal therapy (PTT) and photodynamic therapy (PDT). Compared with PTT and PDT, the novel techniques of sonodynamic therapy (SDT) and photoacoustic therapy (PAT) exhibit amplified ROS generation and precise photoacoustic-shockwaves to enhance anticancer effect when BP receives ultrasound or NIR irradiation. Based on the prospective phototherapy, BP with irradiation can cause a “double-kill” to tumor cells, involving tumor-structure damage induced by heat, ROS, and shockwaves and a subsequent anticancer immune response induced by in situ vaccines construction in tumor site, which is referred to as photoimmunotherapy (PIT). In conclusion, BP shows promise in natural antitumor biological activity, biological imaging, drug delivery, PTT/PDT/SDT/PAT/PIT, nanovaccines, nanoadjuvants, and combination immunotherapy regimens.